Extension of the Period for Consent to Increase Quotas Under the Fourteenth General Review of Quotas, the 2008 Reform of Quota and Voice, and the Eleventh General Review of Quotas. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2014)
This paper proposes a further six-month extension of the period for consent to increase quotas under the Fourteenth General Review of Quotas. The current deadline is due to expire on December 31, 2014; however, Board of Governor's Resolution No. 66-2 provides that the Executive Board may extend the period for consent as it may determine. An extension under Resolution No. 66-2 will also extend the periods of consent for quota increases under the 2008 Reform of Quota and Voice (Resolution No. 63-2) and the Eleventh General Review of Quotas (Resolution No. 53- 2).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Costa Rica